Fever Crumb - Reeve, Philip (New York Scholastic Press, 2010)
Foundling Fever Crumb has been raised as an engineer although females in the future London, England, are not believed capable of rational thought, but at age fourteen she leaves her sheltered world and begins to learn startling truths about her past while facing danger in the present.
1000L
Keywords: Identity (Philosophical concept); Sex role; Technology; Foundlings; Science fiction; London (England); England; Science fiction; Steampunk fiction; Young adult fiction